SOMATIC EMBRYOGENESIS IN LOCAL COWPEA (Vigna unguiculata L. (WALP) VARIETIES - Bala, Isah (FUDMA JOURNAL OF SCIENCES, 2022)
Organogenesis in vitro was evaluated in explants derived from shoot apices of two local cowpea varieties cultured on Murashige and Skoog (MS) basal medium. To evaluate the response of the cowpea genotypes to in vitro regeneration, seedlings were drived from zygotic embryos excised from surface sterilized seeds after two weeks of culture on MS basal medium + vitamins supplement with 30% sucrose. To regenerate shoots, apices of the In Vitro seedlings with average length of 1cm were excised and cultured on MS supplemented with 0.5, 1.0 or 1.5mg/L 6-Benzylamino purine (BAP) with or without 0.1mg/L  Î±-naphthaleneacetic acid (NAA) for six weeks.  Variation was observed in response of the shoot apices from different cowpea cultivars to in vitro regeneration of  shoots. The highest shoot number was recorded with Danilla and shoot length was highest in  Kanannado,  indicating that Danilla responded well to in vitro regeneration.  While there were significant differences between these concentrations and other concentrations used in this study on the number of shoots produced, statistically there was no difference between the traetments  tested on the in vitro shoot length recorded in this study.Although shoots were succesfully regenerated in this study rooting  was not achieved as the explants gradually transformed  into calli
Keywords: Organogenesis, Explant, Somatic Embryogenesis